(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2023)
Human resource management in local government bodies is related to the management of human potential and competencies to achieve the aspirations of local government through recruitment, training and development, performance evaluation and career development functions. Capable, qualified and potential personnel of local authorities make a great contribution to the development and implementation of various socio-economic projects of the regions. Based on this, in this article, the practices of some countries on the management of human resources in local government bodies are studied, and analytical and comparative information is given.